An approach to the concept of social pedagogy - Carlos Juliao Vargas (Corporación Universitaria Minuto de Dios, 2004)
The object of this article is to investigative about the history of the concept social pedagogy. And doing this we can find our own conception and to work with a theoretic discipline but essentially praxeological or of human action. Here we exam not only the evolution of the concept but its implications in the future of the education. If we take into account, what is really important is that students can work in their social practices, and in this way, to know and to face the social reality of the country and in this manner can contribute in the construction of a new society. The analysis that is presented is a contribution to the debate that is being developed in Europe around the question what gives the social to the pedagogy or to the educative? So, it can be appreciate, how a doctrine and a discipline is being conform at the same time when working following the object of social pedagogy, taking as a focus the pedagogy praxis and theoretic-practical proposal that are being discussed.